Extending dynamic network theory to group and social interaction analysis: Uncovering key behavioral elements, cycles, and emergent states. (February 2016) - Westaby, James D.; Woods, Naomi; Pfaff, Danielle L.
This article proposes a markedly new conceptual approach to group and social interaction analysis, grounded in transformative advances in dynamic network theory. The framework first theoretically identifies the small set of behavioral elements that can be influential across social contexts. Example behavioral elements include goal striving to advance a communication or viewpoint, system supporting of others, goal preventing, and affect-based system negating. The framework distinctively allows researchers to simultaneously combine the elements to explain complex units, such as a person disagreeing with another (goal prevention), but in a warm and caring way (system support). The approach also provides new insight into how behavioral elements elapse over time, such as our distinct characterization of support cycles (e.g., reinforcement, comfort, and submissive) and conflict cycles (e.g., basic, heated, and acidic). The approach uniquely demonstrates how lower-level behavioral elements can be used to predict higher-level emergent states and climates, such as hostile climates.